Fresno County Bar Association Sponsored Fresno Courthouse Historical Display Case - Watkins, Howard::::::::: (1989)
Display of information on Fresno County Bar Association's Attorney Referral Service and State Bar pamphlets and plaque of Fresno County Bar Association Presidents through 1989